A Place for Inquiry, A Place for Wonder : The Andrews Forest - Robbins, William G., 1935- (Book collections on Project MUSE., 2020)
"The H.J. Andrews Experimental Forest is a slice of classic Oregon: due east of Eugene in the Cascade Mountains, the Andrews Forest comprises almost 16,000 acres of the Lookout Creek watershed. The landscape is steep, with hills and deep valleys and cold, fast-running streams. The densely forested landscape includes cedar, hemlock, and moss-draped ancient Douglas fir trees. One of eighty-one USDA experimental forests, the Andrews is administered cooperatively by the US Forest Service, Oregon State University, and the Willamette National Forest. While many Oregonians may think of the Andrews simply as a good place for a hike, research conducted there has profoundly reshaped Forest Service management policies and contributed to our understanding of healthy forests"--